Temperature Dependence of PECVD Grown Boron Nitride Film in MIS structure - Ozdemir, Orhan; Bozkurt, Bora; Yilmazer, Deneb; Gokdemir, Pinar; Kutlu, Kubilay (AMER INST PHYSICS, 2009)
PECVD grown boron nitride (BN) film was Investigated as dielectric film in the form of metal/insulator/p-silicon (MIS) structures AC admittance of MIS structure was measured as a function of dc gate bias voltages and frequencies (1-1000 kHz) of the superimposed ac bias voltage (10 mV). For each applied bias voltage (from accumulating to inverting bias regimes), temperature (T) dependence of both capacitance (Cm) and conductance (G ) were measured to investigate majority/minority carrier behavior under various frequencies (kHz-MHz) as parameters. Cm(Gmko)-T-co measurements revealed that observed capacitance steps and conductance peaks were related to traps residing at the interface of insulator/semiconductor structure. On the other hand, surface band bending tv, of silicon and activation energy (EA) deduced from the Arrhenius plot of the frequency vs. reciprocal temperature as a function of gate bias (VG) seemed linearly dependent, implying that EA reflected the surface band bending (14/5) vanation.
Keywords: freeze out; capacitance-temperature; surface band bending; activation energy; boron nitride; Physics